Effects of Lactobacillus gasseri OLL2809 and α-lactalbumin on university-student athletes: a randomized, double-blind, placebo-controlled clinical trial - Sashihara, Toshihiro; Nagata, Masashi; Mori, Takeshi; Ikegami, Shuji; Gotoh, Minoru; Okubo, Kimihiro; Uchida, Masayuki; Itoh, Hiroyuki (Applied physiology, nutrition, and metabolism, 2013)
Strenuous exercise reduces immune cell function and increases the risk of respiratory and gastrointestinal infections. In addition, it affects mood state and causes physical fatigue. Athletes require both mental and physical conditioning to execute good performance. In this study, we conducted a randomized, double-blind, placebo-controlled clinical trial to evaluate the immunopotentiation and fatigue-alleviation effects of Lactobacillus gasseri OLL2809 (LG2809) and α-lactalbumin (αLA) in university-student athletes after strenuous exercise. A total of 44 university students who performed strenuous exercise daily were separated into 3 groups to receive a 4-week course of placebo, 100 mg LG2809, or 100 mg LG2809 in combination with 900 mg αLA, respectively. Before and after each dietary treatment, the subjects performed strenuous cycle ergometer exercise for 1 h. Before and after each exercise session, blood samples and visual analogue scale scores for fatigue were obtained. In addition, the mood of each subject before and after the dietary treatment was evaluated using the Profile of Mood States (POMS) questionnaire. LG2809 ingestion was effective in preventing reduced natural killer cell activity due to strenuous exercise and elevating mood from a depressed state. In addition, LG2809 + αLA was found to alleviate minor resting fatigue, which was supported objectively by the significant reduction in the serum reactive oxygen metabolites and transforming growth factor β1 levels. These effects could be helpful for athletes to maintain mental and physical condition.